Network philosophy as a subject methodological reflection in the contest call information society - Yaskevich, Yadwiga S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the status and the problem field of innovation model of network philosophy. Reveals methodological role and purpose of the network of philosophy in understanding the communicative practices of the network economy, politics, culture. The thesis of the need to develop rules and regulators netiquette. Network philosophy is treated as the generalized system of human views on virtual reality, aimed at identifying its nature, the characteristicsof the description (narrative) and of the knowledge, study of social and cultural values of the network of communication, study human and social control mechanisms through the use of possibilities of network effects and the formation of the basic attitudes of people, their beliefs, ideals, principles, knowledge and evaluation of material and spiritual events.
Keywords: virtual reality; organizational structure; culture network; the network philosophy; political space; network economy; management; e-government; Internet ethics